The Role Of Sociology Teachers In Fostering Social Attitudes In The Sociology Learning Process For Class X IPS At Pontianak Islamic High School - Yeni, Yeni; Bahari, Yohanes; Okianna, Okianna (International Journal of Learning and Instruction (IJLI), 2024)
The sociology teacher carries out his   a role model, motivator and guide in developing the social attitudes of class X IPS students. The role of the sociology teacher is as a guide in developing the social attitudes of class X IPS students with several strategies, good examples of discipline and self-confidence. The role of teacher as a motivator in developing the social attitudes of class The role of the teacher as a guide in developing the social attitudes of class. The roles of the teacehr as a role model, motivator, and guide in developing students"™ social attitudes with the application and expertise of the   sociology teacher is considered to be going well because the students are seen to be able to apply and learn the social attitudes that have been taught by the sociology teacher. The approach in this research is by type descriptive qualitative research. Meanwhile , data collection technique use observation, interviews and documentation techniques. Research analysis by reduction, data presentation and conclusion drawing and verification. The primary data sources in this research are sociology teachers and students in class X IPS at SMA Islamiyah Pontianak.Keywords: Teacher"™s Role, Social Attitudes